Total Knee Arthroplasty with Extra- or Intra-Articular Correction Technique for Arthritic Knees with Extra-Articular Deformity of the Femur or Tibia: A Report of Three Cases - Piti Rattanaprichavej; Artit Laoruengthana (Journal of Orthopaedic Surgery, 2016)
This study reports 3 patients who underwent total knee arthroplasty combined with extra- or intra-articular correction technique for arthritic knees with extra-articular deformity of the femur or tibia.